2000
DOI: 10.1054/jhsb.2000.0485
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation of Intra Articular and Unstable Fractures of the Distal Radius Using the AO Distal Radius Plate

Abstract: This study reports the results of open reduction and internal fixation of 25 dorsally displaced distal radial fractures using a specifically designed plate for the distal radius, the AO pi plate (Synthes Ltd, Paoli, USA). Twenty-one of these fractures were complex and intra-articular (AO Type 'C'). Measurement of range of motion of the affected wrist at an average follow-up of 16 months revealed a median return of 60 degrees of wrist extension, 40 degrees of wrist flexion, 90 degrees of pronation and 90 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 21 publications
3
58
0
4
Order By: Relevance
“…Tenosynovitis and extensor tendons ruptures had received an extensive attention in recent papers (25,29,30,31). Tendinitis resulting in need for plate removal had been reported in up to 20 % to 33 % of cases (17,25). To prevent this complication, some authors suggested an early implant removal (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenosynovitis and extensor tendons ruptures had received an extensive attention in recent papers (25,29,30,31). Tendinitis resulting in need for plate removal had been reported in up to 20 % to 33 % of cases (17,25). To prevent this complication, some authors suggested an early implant removal (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although meta-analysis has failed to show superiority of specifi c operative treatment method (15), Jupiter (3,16) and other researchers (5,17,18) acknowledged that open reduction and internal fi xation with plates has obvious advantages over the other methods of distal radius fracture fi xation. It allows a direct restoration of anatomy, stable internal fi xation, shorter immobilization period, and thus an earlier return of wrist function.…”
Section: Introductionmentioning
confidence: 99%
“…We observed these injuries to be occurring more commonly in males in their early middle age of 40s. [7,8] In our study operative group 11 (61%) out of 18 cases had fracture styloid process of ulna, 2 male cases had fracture tibial plateu, 2 male & 2 female cases had fracture shaft of humerus, 2 male cases had fracture leg bone & 2 cases (one male & one female) fracture shaft of femur. Most of the cases were of ipsilateral side.…”
Section: Methodsmentioning
confidence: 63%
“…23 For unstable distal radial fractures, closed reduction has been reported to compromise functional return and result in malunion in up to 50%. 24,21,25 Treatment options include percutaneous wiring, reported as ineffective in osteoporotic bone, 26,27 dorsal plate fixation, which can lead to attrition ruptures of extensor tendons, 28 and external fixation, which carries the risk of pin tract infection and wrist stiffness. 29 One option for treating these complex fractures is by open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%